Associations of vegetable and fruit intake with cognitive function and its decline: Two longitudinal studies - Liyan Huang; Caifeng Zhao; Mengyan Gao; Yang Tao; Xiao Chen; Hui Chen; Fengping Li; Ying Zheng; Mengxi Lu; Yuan Ma; Shuang Rong; Changzheng Yuan (Elsevier, 2024)
Objectives: Previous studies suggested protective associations of vegetables and fruits (VF) intake with cognitive function, but evidence on specific types of VF was insufficient. Methods: The current study included 4066 participants from 1997 to 2006 in the China Health and Nutrition Survey (CHNS) and 6170 participants from 2013 to 2020 in the Health and Retirement Study (HRS). Dietary intake (using 3-day 24-h dietary recalls in CHNS and food frequency questionnaire in HRS) and cognitive function (using the Telephone Interview for Cognitive Status-Modified, TICS-m) were measured. Linear mixed-effects models were used to estimate the beta coefficients (β) and the 95% confidence intervals (CI) to evaluate the association of VF with cognitive function (z-score) and its decline. Results: Highest intake of total VF was associated with better cognitive function and slower cognitive decline. Differences in cognitive function z-score between the highest and lowest tertiles of VF consumption were 0.039 (95% CI: 0.002, 0.076) for CHNS and 0.063 (95% CI: 0.026, 0.100) for HRS. The corresponding differences in annual cognitive decline were 0.011 (95% CI: 0.002, 0.021) and 0.012 (95% CI: 0.003, 0.020) units respectively. Vegetables and fruits showed independent associations with cognitive function and its decline. In specific VF subgroups, when comparing the highest to the lowest tertile intake, cruciferous vegetables (β = 0.058, 95% CI: 0.017, 0.100 in CHNS and β = 0.067, 95% CI: 0.032, 0.101 in HRS) and green leafy vegetables (β = 0.036, 95% CI: −0.001, 0.073 in CHNS and β = 0.082, 95% CI: 0.046, 0.117 in HRS) was associated with better cognitive function in both cohorts. Similarly, higher intake of dark-colored vegetables (β = 0.019, 95% CI: 0.008, 0.030 for red/yellow vegetables in CHNS and β = 0.004, 95% CI: 0.001, 0.007 for green leafy vegetables in HRS) were associated with slower cognitive decline in subsequent years. Moreover, rigorous sensitivity analyses confirmed the stability of the results. Conclusions: Our findings support the potential beneficial roles of VF, especially cruciferous vegetables, green leafy vegetables, and red/yellow vegetables, in maintaining cognitive function and slowing cognitive decline in middle-aged and older adults.